Conductive hydrogel and preparation method thereof, flexible electrochemical sensor and application of flexible electrochemical sensor in glucose detection

By using Ga-grafted MXene's CS hydrogel as working electrode material, a three-dimensional chain structure is formed, which solves the problems of rigidity and vulnerability of working electrode materials in traditional electrochemical sensors, and achieves flexible electrochemical with high sensitivity and long-term stable detection. sensor.

CN119490699APending Publication Date: 2025-02-21SHANGHAI INST OF MICROSYSTEM & INFORMATION TECH CHINESE ACAD OF SCI
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411624289.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The working electrode materials of existing flexible electrochemical sensors are rigid and cannot effectively fit the skin, affecting sweat absorption and detection performance; the surface of the working electrode is prone to fracture and wear, reducing conductive performance and reliability.

Method used

The CS hydrogel of Ga-grafted MXene is used as the working electrode material to form a three-dimensional chain structure, and the liquid metal gallium and MXene sheet-like structure are connected to improve conductivity and ductility.

Benefits of technology

It realizes high sensitivity and long-term stable detection of flexible electrochemical sensors, which can effectively fit the skin, reduce wear, improve the service life of the electrode, and reduce costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490699A_ABST
    Figure CN119490699A_ABST
Patent Text Reader

Abstract

The invention relates to conductive hydrogel, which is CS hydrogel of Ga grafted MXene, Ga is liquid metal gallium, MXene is Ti3C2Tx, Tx is-F,-OH or-O, CS is chitosan, a two-dimensional sheet structure of single-layer MXene provides a chain, and adjacent chains are connected through liquid metal Ga spheres to provide a three-dimensional chain structure of the conductive hydrogel. The invention also relates to the conductive hydrogel, a preparation method thereof, a flexible electrochemical sensor and application of the flexible electrochemical sensor in glucose detection. According to the invention, disease markers such as glucose in human sweat can be rapidly detected with high sensitivity for a long time, the operation is simple, professional workers are not needed, and real-time daily monitoring can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an electrochemical sensor, and more specifically to a conductive hydrogel and a preparation method thereof, and a flexible electrochemical sensor and application thereof in glucose detection. Background Art

[0002] Flexible electrochemical sensors have the advantages of miniaturization, portability, real-time monitoring and non-invasive detection, which meet people's strong demand for real-time acquisition of their own biochemical information and constant attention to their health status in non-hospital environments. In order to monitor the health status of the human body in all aspects, the rapid detection of chemical substances and biomarkers (such as glucose, lactate, cortisol, dopamine, potassium and sodium, etc.) in human sweat through electrochemical sensors has good research prospects. At present, wearable electrochemical sensors have been developed and applied to estimate and monitor biomarkers such as glucose, cortisol and lactate in sweat. Although these sensors have achieved certain research results, there are still two problems: First, the working electrode materials are made of rigid materials, which cannot fit the skin well during the detection process, affecting the absorption and detection performance of sweat; second, the working electrode surface will also have different degrees of fracture and wear, reducing the conductivity and reliability of the electrode. In response to the above problems, there is currently no widely used flexible electrochemical sensor with strong reliability, high conductivity and high ductility in the industry. Summary of the invention

[0003] In view of the above-mentioned shortcomings of the prior art, the object of the present invention is to provide a conductive hydrogel and a preparation method thereof, a flexible electrochemical sensor and an application thereof in glucose detection.

[0004] The conductive hydrogel according to the present invention is a CS hydrogel of Ga-grafted MXene, wherein Ga is liquid metal gallium and MXene is Ti3C2T x , T x is -F, -OH or -O, CS is chitosan, the two-dimensional sheet structure of the single-layer MXene provides chains, and adjacent chains are connected by liquid metal Ga balls to provide the three-dimensional chain structure of the conductive hydrogel.

[0005] In a preferred embodiment, the spacing between adjacent chains is 10 μm to 50 μm.

[0006] In a preferred embodiment, the diameter of the Ga ball is 1 μm to 3 μm.

[0007] The preparation method of the conductive hydrogel according to the present invention comprises the following steps: S1, adding chitosan to a dilute acetic acid solution to obtain a chitosan hydrogel solution; S2, adding a MXene dispersion to the chitosan hydrogel solution to obtain a chitosan hydrogel solution of MXene; S3, adding a Ga ball dispersion to the chitosan hydrogel solution of MXene to obtain a Ga@MXene / CS hydrogel.

[0008] In a preferred embodiment, in step S1, the concentration of the chitosan hydrogel solution is 0.3 g / mL-1.2 g / mL.

[0009] In a preferred embodiment, in step S3, liquid metal Ga is dispersed in an ethanol solution and ultrasonically vibrated to obtain a Ga ball dispersion solution.

[0010] In a preferred embodiment, in step S3, the volume ratio of the Ga ball dispersion to the MXene chitosan hydrogel solution is 1:2 to 1:10.

[0011] The flexible electrochemical sensor according to the present invention comprises a working electrode, a reference electrode and an auxiliary electrode, wherein the conductive hydrogel is used as the working electrode and arranged between the reference electrode and the auxiliary electrode, Ag / AgCl is used as the reference electrode, and the conductive carbon paste is used as the auxiliary electrode.

[0012] According to the application of the above-mentioned flexible electrochemical sensor of the present invention in glucose detection, the detection range of glucose concentration is 10 μM-1000 μM.

[0013] In a preferred embodiment, the application includes applying the flexible electrochemical sensor to the wearable field to directly detect sweat produced by the human body.

[0014] The flexible electrochemical sensor according to the present invention can fit the skin well and is not prone to wear. It uses Ga@MXene / CS conductive hydrogel as the working electrode, and improves the service life of the electrode while ensuring the electrical performance of the electrode. It has a simple preparation process, high reliability, low cost, and wide practical application. It can quickly, highly sensitively, and long-term detect disease markers such as glucose in human sweat. It is simple to operate, does not require professional staff, and can be used for real-time daily monitoring. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 It is a schematic diagram of the preparation process of Ga@MXene / CS hydrogel according to the present invention.

[0016] Figure 2 : The SEM image and element distribution diagram of the Ga@MXene / CS hydrogel according to the present invention.

[0017] Figure 3aIt is shown that the flexible electrochemical sensor according to the present invention has a wider detection range when detecting glucose.

[0018] Figure 3b It is shown that the flexible electrochemical sensor according to the present invention has higher sensitivity in detecting glucose.

[0019] Figure 4a Schematic diagram of the application of a wearable flexible electrochemical sensor according to the present invention.

[0020] Figure 4b The feasibility of the wearable flexible electrochemical sensor according to the present invention in detecting glucose in actual sample analysis is shown. DETAILED DESCRIPTION

[0021] The following is an explanation of the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in the present embodiment only illustrate the basic concept of the present invention in a schematic manner, and only the components related to the present invention are shown in the figure instead of being drawn according to the number, shape and size of the components in the actual implementation. The type, quantity and proportion of each component in the actual implementation can be a random change, and the component layout type may also be more complicated.

[0022] The present invention provides a conductive hydrogel with a chain structure, which is a Ga-grafted MXene CS (Ga@MXene / CS) hydrogel, wherein Ga is liquid metal gallium, and MXene is Ti3C2T x , T x is -F, -OH or -O, CS is chitosan, the conductive hydrogel is a three-dimensional chain structure, the two-dimensional sheet structure of the single-layer MXene provides chains, and adjacent chains are connected by liquid metal Ga balls. In a preferred embodiment, the spacing between adjacent chains is 10-30μm, 30-70μm, 70-90μm, 90-120μm, 90-95μm, 95-100μm, 100-105μm, 105-110μm, 110-115μm or 115-120μm. In a preferred embodiment, the diameter of the Ga ball is 1.5-2.5μm, 1.5-1.7μm, 1.7-1.9μm, 1.9-2.1μm, 2.1-2.3μm or 2.3-2.5μm. It should be understood that the spacing between chains is related to the distribution and relative concentration of MXene and gallium spheres. The larger the diameter of the gallium spheres, the smaller the spacing between chains; the higher the concentration of MXene, the smaller the spacing between chains will be.

[0023] Preparation of Ga@MXene / CS hydrogel

[0024] See also Figure 1 , dissolve glacial acetic acid in deionized water and stir to obtain a dilute acetic acid solution with a concentration of 2-4%, 2-2.5%, 2.5-3%, 3-3.5% or 3.5-4%. Add chitosan to the dilute acetic acid solution while heating in water areas of 60-70°C, 65-65°C or 65-70°C, and stir for 25-35min, 25-30min, 30-35min to obtain a chitosan hydrogel solution. Add the MXene dispersion to the chitosan hydrogel solution and stir ultrasonically to obtain a chitosan hydrogel solution of MXene. Disperse liquid metal Ga in an ethanol solution and then ultrasonically oscillate for 30-60min, 30-35min, 35-40min, 40-45min, 45-50min, 50-55min or 55-60min to obtain a Ga ball dispersion solution with a concentration of 0.02g / mL to 0.2g / mL. The Ga ball dispersion is added to the chitosan hydrogel solution of MXene to obtain Ga@MXene / CS hydrogel. In a preferred embodiment, the MXene dispersion is commercially available titanium carbide (Ti3C2T x )MXene thin layer dispersion, CAS number is 12363-89-2. The MXene dispersion in the following examples is purchased from Xinxin Technology Co., Ltd. In a preferred embodiment, the concentration of the chitosan hydrogel solution is 0.3g / mL-1.2g / mL. For example, 0.3g / mL-0.4g / mL, 0.4g / mL-0.5g / mL, 0.5g / mL-0.6g / mL, 0.6g / mL-0.7g / mL, 0.7g / mL-0.8g / mL, 0.8g / mL-0.9g / mL, 0.9g / mL-1.0g / mL, 1.0g / mL-1.1g / mL or 1.1g / mL-1.2g / mL. In a preferred embodiment, the volume ratio of the Ga ball dispersion to the MXene chitosan hydrogel solution is 1:2 to 1:10.

[0025] Example 1

[0026] Dissolve 1 mL of glacial acetic acid in 50 mL of deionized water and stir for 30 min to obtain a dilute acetic acid solution. Add 0.3 g of chitosan to 40 mL of dilute acetic acid solution in a 65 °C water bath and stir for 30 min to obtain a chitosan hydrogel solution with a concentration of 0.3 g / mL. Add the Ti3C2F dispersion to the chitosan hydrogel under ultrasonic stirring, and continue magnetic stirring the mixture for 30 minutes to obtain a Ti3C2F / CS hydrogel. Disperse 0.6 g of liquid metal Ga in an ethanol solution (5 mL) and then ultrasonically oscillate for 30 min to obtain an ethanol solution of Ga balls. Add 5 mL of the ethanol solution of Ga balls to 10 mL of the Ti3C2F / CS hydrogel solution in a 50 °C water bath to obtain a Ga@Ti3C2F / CS hydrogel.

[0027] The scanning electron microscopy image and element distribution map of the obtained Ga@MXene / CS hydrogel are shown in the attached figure. Figure 2 As shown. Figure 2 a and Figure 2 b It can be seen that the surface of Ga@MXene / CS hydrogel presents a three-dimensional porous structure as a whole, in which the single-layer MXene builds the three-dimensional porous structure of the hydrogel, and the liquid metal Ga balls connect the dispersed single-layer MXene together by electrostatic force to form a chain structure (see Figure 2 c). Figure 2 In c, the distance between chains is maintained at 10-50 μm, and the size of Ga balls is 1-3 μm, which indicates that Ga balls connect the dispersed MXene nanosheets together to form a three-dimensional conductive structure. Figure 2 d- Figure 2 i shows the element distribution on the surface of the hydrogel. MXene is composed of elements Ti, C, F and O, and the liquid metal ball is composed of element Ga. From the element distribution diagram of the hydrogel, it can be seen that the liquid metal Ga connects the sheet-like MXene structure.

[0028] Fabrication of flexible electrochemical sensors

[0029] The Ga@MXene / CS hydrogel prepared above is coated on a flexible printed circuit board as a working electrode S of a flexible electrochemical sensor. In a preferred embodiment, the line width of the working electrode S is 0.2 to 1.5 mm, for example, 300 to 350 μm, 350 to 400 μm, 400 to 450 μm, 450 to 500 μm, 500 to 550 μm, 550 to 600 μm, 600 to 650 μm or 650 to 700 μm.

[0030] The flexible electrochemical sensor according to the present invention is an integrated micro wearable flexible electrochemical sensor, which also includes a reference electrode M and an auxiliary electrode T, wherein the working electrode S is arranged between the reference electrode M and the auxiliary electrode T to ensure that the signals between the electrodes will not interfere. The spacing between the working electrode S and the reference electrode M is 200nm to 800nm, for example, 200 to 350nm, 350 to 500nm, 500 to 650nm or 650 to 800nm. The spacing between the working electrode S and the auxiliary electrode T is 200nm to 800nm, for example, 200 to 350nm, 350 to 500nm, 500 to 650nm or 650 to 800nm.

[0031] The conductive silver paste is coated on the position of the reference electrode on the flexible printed circuit board to form a silver layer, and dried at a temperature of 100-130°C, 100-105°C, 105-110°C, 110-115°C, 115-120°C, 120-125°C or 125-130°C for 1-2h, 1-1.2h, 1.2-1.4h, 1.4-1.6h, 1.6-1.8h or 1.8-2.0h, and then the conductive silver paste is coated on the position of the reference electrode on the flexible printed circuit board to form a silver layer, and ... L or 0.4-0.5 mol / L FeCl3 solution is dropped into the silver layer, the silver layer is completely immersed in the FeCl3 solution for 50-70s, 50-55s, 55-60s, 60-65s or 65-70s, washed with deionized water, and dried at 25-70°C, 25-30°C, 30-35°C, 35-40°C, 40-45°C, 45-50°C, 50-55°C, 55-60°C, 60-65°C or 65-70°C for 1-3h, 1-2h or 2-3h, and the obtained Ag / AgCl is used as the reference electrode M of the flexible electrochemical sensor. In a preferred embodiment, the line width of the reference electrode M is 0.2-1.5mm. For example, it is 300 to 350 μm, 350 to 400 μm, 400 to 450 μm, 450 to 500 μm, 500 to 550 μm, 550 to 600 μm, 600 to 650 μm, or 650 to 700 μm.

[0032] The conductive carbon paste is evenly applied to the position of the auxiliary electrode, and dried at room temperature to obtain the auxiliary electrode T of the flexible electrochemical sensor. In a preferred embodiment, the line width of the auxiliary electrode T is 0.2-1.5 mm, for example, 300-350 μm, 350-400 μm, 400-450 μm, 450-500 μm, 500-550 μm, 550-600 μm, 600-650 μm or 650-700 μm.

[0033] Flexible electrochemical sensor for glucose detection

[0034] The flexible electrochemical sensor whose working electrode is Ga@MXene / CS hydrogel according to the present invention exhibits good glucose detection performance, high sensitivity and wide linear detection range, and is suitable for the detection and quantitative analysis of glucose in human sweat.

[0035] like Figure 3a-Figure 3b As shown in the figure, the detection performance of the flexible electrochemical sensor was measured by differential pulse voltammetry (DPV) in PBS buffer at pH = 7.4. Figure 3a It can be seen that when the glucose concentration increases from 10μM to 1000μM, the detection current of DPV increases from 8μA to 23.5μA. Figure 3b It can be seen that the detection current of DPV is proportional to the glucose concentration, and the linear fitting equation is I (μA) = 0.013C Glucose +9.845, the detection limit is 0.77μM, the sensitivity is 1.122μA·μM-1·cm-2, and the linear range of detection is 10–1000μM, which meets the detection requirements of human sweat.

[0036] Applications of wearable flexible electrochemical sensors

[0037] The chip resistor is welded to the flexible printed circuit board by welding to form a heater I, so that the heater I is connected to the flexible electrochemical sensor, and the heater I is connected to a constant voltage power supply to stimulate the human body to produce a large amount of sweat, and the sweat generated by heating flows into the flexible electrochemical sensor through the heater I, and the flexible electrochemical sensor is connected to the electrochemical workstation, which is applied to the wearable field to directly detect the sweat produced by the human body. Simple operation, no professional staff is required, real-time daily monitoring can be performed, and no invasive blood sampling is required every day, reducing the pain of diabetics. In a preferred embodiment, the resistance of the chip resistor is 50 to 500Ω. For example, 50 to 100Ω, 150 to 200Ω, 200 to 250Ω, 250 to 300Ω, 300 to 350Ω, 350 to 400Ω, 400 to 450Ω or 450 to 500Ω. In a preferred embodiment, the line width of the heater I is 0.2 to 1.5mm. For example, it is 300 to 350 μm, 350 to 400 μm, 400 to 450 μm, 450 to 500 μm, 500 to 550 μm, 550 to 600 μm, 600 to 650 μm, or 650 to 700 μm.

[0038] like Figure 4a and Figure 4bAs shown, the flexible electrochemical sensor is connected to an electrochemical workstation and a computer to diagnose glucose in sweat. A heater is used to stimulate the human body to produce sweat, and the sweat flows into the surface of the flexible electrochemical sensor, and the glucose detection signal in the sweat is tested by the micro electrochemical workstation. Differential pulse voltammetry (DPV) is used to measure the glucose concentration of four types of sweat. The measured values ​​are close to the standard values, indicating that the measurement is accurate. The recovery rate of the detector ranges from 88% to 99.6%, showing the feasibility of the glucose sensor of the present invention in actual sample analysis.

[0039] In summary, the present invention realizes high-sensitivity detection of trace sweat by designing a conductive hydrogel working electrode with a lock-and-chain structure, and realizes real-time detection of microsensors in conjunction with a flexible printed circuit board and a commercial micro-electrochemical workstation. The present invention utilizes the conductivity of liquid metal and the ductility of hydrogel to solve the technical problems of conductivity and reliability of traditional rigid working electrode materials. The wearable flexible electrochemical sensor for glucose detection of the present invention uses sweat to replace blood, does not require daily invasive blood collection, reduces the pain of diabetics, and can directly detect trace sweat produced by human metabolism on a daily basis. The flexible electrochemical sensor for glucose detection of the present invention is simple to operate, does not require professional staff, can be monitored in real time on a daily basis, and has a simple preparation process, does not require a bonding and packaging process, is low-cost, has high reliability and stability, and has great practical applications. The wearable flexible electrochemical sensor for glucose detection of the present invention can quantitatively detect glucose in trace sweat. Furthermore, a microfluidic device can be combined to achieve separation and detection of multiple substances in sweat.

[0040] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A conductive hydrogel, characterized in that: The conductive hydrogel is a CS hydrogel of Ga-grafted MXene, wherein Ga is liquid metal gallium and MXene is Ti3C2T x , T x is -F, -OH or -O, CS is chitosan, the two-dimensional sheet structure of the single-layer MXene provides chains, and adjacent chains are connected by liquid metal Ga balls to provide the three-dimensional chain structure of the conductive hydrogel.

2. The conductive hydrogel according to claim 1, characterized in that: The spacing between adjacent chains is 10 μm to 50 μm.

3. The conductive hydrogel according to claim 1, characterized in that: The diameter of the Ga ball is 1 μm to 3 μm.

4. A method for preparing a conductive hydrogel according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: S1, adding chitosan to a dilute acetic acid solution to obtain a chitosan hydrogel solution; S2, adding the MXene dispersion into the chitosan hydrogel solution to obtain a chitosan hydrogel solution of MXene; S3, adding the Ga ball dispersion into the chitosan hydrogel solution of MXene to obtain Ga@MXene / CS hydrogel.

5. The preparation method according to claim 4, characterized in that: In step S1, the concentration of the chitosan hydrogel solution is 0.3 g / mL-1.2 g / mL.

6. The preparation method according to claim 4, characterized in that: In step S3, liquid metal Ga is dispersed in an ethanol solution and ultrasonically vibrated to obtain a Ga ball dispersion solution.

7. The preparation method according to claim 4, characterized in that: In step S3, the volume ratio of the Ga ball dispersion to the MXene chitosan hydrogel solution is 1:2 to 1:

10.

8. A flexible electrochemical sensor comprising a working electrode, a reference electrode and an auxiliary electrode, characterized in that: The conductive hydrogel according to any one of claims 1 to 3 is arranged as a working electrode between a reference electrode and an auxiliary electrode, Ag / AgCl is used as a reference electrode, and a conductive carbon paste is used as an auxiliary electrode.

9. Application of the flexible electrochemical sensor according to claim 8 in glucose detection, characterized in that: The detection range of glucose concentration is 10μM-1000μM.

10. The use according to claim 9, characterized in that: The application involves applying flexible electrochemical sensors to the wearable field to directly detect sweat produced by the human body.

Citation Information

Cited By

  • Preparation method and application of MXene / liquid metal-based flexible composite film

    CN121687649A

  • Method for preparing mxene / liquid metal-based flexible composite film and application thereof

    CN121687649B